SNR G54.1+0.3, a PeVatron Candidate Unveiled by LHAASO - Yihan Shi; Yudong Cui; Lili Yang (The Astrophysical Journal)
Recently, the LHAASO Collaboration reported the first very-high-energy gamma-ray catalog, containing 90 TeV sources. Among these sources, 1LHAASO J1929+1846u is located 0 $\mathop{.}\limits^{\unicode{x000b0}}$ 3 west of SNR G54.1+0.3 and also lies within a  +53 km s ^−1 cloud (the Western Cloud). Moreover, one of the IceCube track-type high-energy starting events is found around 1 $\mathop{.}\limits^{\unicode{x000b0}}$ 3 north of 1LHAASO J1929+1846u, which may serve as strong evidence for the hadronic origin of this TeV source. SNR G54.1+0.3 is a young supernova remnant (SNR), with a powerful pulsar wind nebula (PWN) inside. Its X-ray radiation from the PWN and the SNR shell can be clearly identified. The radio emission from the PWN region is also given. However, given the angular resolution of gamma-ray experiments, the entire SNR region is viewed as a point source by the Fermi Large Area Telescope, High Energy Stereoscopic System, and VERITAS. In this work, we explore a hybrid scenario where SNR G54.1+0.3 is indeed associated with the Western Cloud, and we derive the multiwavelength emissions from the PWN, the SNR shell, and the Western Cloud, separately. Our model can explain the observations well, indicating that SNR G54.1+0.3 might be an excellent candidate of the Galactic PeVatron and neutrino source.